A New Politics of GCC Economic Statecraft: The Case of UAE Aid and Financial Intervention in Egypt. Issue 1 (2nd January 2017) - Young, Karen E.
Abstract: The Arab Gulf States (AGS), or the member states of the Gulf Cooperation Council (GCC) (Saudi Arabia, Kuwait, Oman, Bahrain, Qatar and the United Arab Emirates), have historically used foreign aid and humanitarian aid as a quiet tool of their respective foreign policies within the wider Middle East. More recently, however, we have seen targeted financial aid and military assistance by these states, particularly Saudi Arabia, Qatar and the United Arab Emirates, towards neighbours in crisis. Looking at the expansion of GCC state aid in the wider region after 2011 in the historical context of oil wealth windfalls, the article offers a close case study of UAE aid and financial intervention in Egypt. UAE aid and investment ties to Egypt are part of a growing strategic commitment linking Emirati domestic economic interests and security interests, particularly on counter-terrorism and weakening extremist ideologies. The flexibility of Emirati economic statecraft reflects a willingness to reduce support, especially when the investment opportunities are not seen as profitable to the state and its related entities. Arguably, the Emirati approach to Egypt presents a new form of conditionality, less interested or invested in the implementation of fiscal reform or political inclusion, and more concerned with advancing the twin goals of state-led capitalism and a regional vision of secular Arab leadership.